Preference of Generation Z Towards Social Interaction - Generose C. Billano; Jester John P. Cogollo; Eljan Michael C. Dela Cruz; Monica Lauren P. Manahan; Seith Nathaniel D. Romualdo; Tonette Jye T. Rizaldo; Sir Hassanal P. Abusma; Sir Mark F. Onia (Indonesian Journal of Community and Special Needs Education, 2021)
The purpose of this study was to determine the preferred mode of interaction of generation Z. There are four novelties: (1) To understand the percentage of students who prefer social media as a medium of social interaction, (2) To know the percentage of students who prefer face-to-face interaction, (3) To comprehend what medium do they prefer to use when they are discussing their courtship involvement, academic matters, personal issues, interpersonal relational conflicts, sex-related matters, and (4) To know the reasons for students' preference in terms of mode of Interaction. The study used a mixed-method approach, employed explanatory design, and used simple random sampling in choosing the 76 respondents/participants from the Sultan Kudarat State University (SKSU) students. A survey and an interview were conducted to compare face-to-face interaction and social media interaction as the primary mode of interaction. The results showed that 60 students prefer face-to-face interaction over 76 students, with a frequency of 78.94% out of 100%. It is concluded that most of the students prefer face-to-face social interaction rather than social media. This study has an impact on Generation Z, as it serves as a realization of their social activeness in interaction as well as on the community. Also, it will help society understand how Generation Z compares to other generations by being the generation most affected by technology and its rapidly evolving form of communication, as well as the loss of their ability to communicate.